2011
DOI: 10.1590/s1677-54492011000300010
|View full text |Cite
|
Sign up to set email alerts
|

High origin of the deep femoral artery: a case report and literature review

Abstract: Arterial variations of the femoral triangle are rarely reported in the literature. In the present article, we have reported a case of high origin of the deep femoral artery, which was originating just lower to the inguinal ligament. It was also observed that the lateral circumflex femoral artery arose directly from the femoral artery instead from the deep femoral artery. We have discussed the anatomy, embryological basis, and clinical implications of these variations along with relevant literature review. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…A ATC de múltiplos detectores ou angiografia é especialmente recomendada para evidenciar a presença de outros aneurismas e lesões arteriais estenóticas ou oclusivas 3,7 . É necessário atentar-se também à anatomia e suas alterações, visto que há descrição de variações anatômicas nessa área que podem levar a desastres durante procedimentos, caso não tenham sido identificadas previamente 14 .…”
Section: Discussionunclassified
“…A ATC de múltiplos detectores ou angiografia é especialmente recomendada para evidenciar a presença de outros aneurismas e lesões arteriais estenóticas ou oclusivas 3,7 . É necessário atentar-se também à anatomia e suas alterações, visto que há descrição de variações anatômicas nessa área que podem levar a desastres durante procedimentos, caso não tenham sido identificadas previamente 14 .…”
Section: Discussionunclassified
“…The erect posture verified in these primates requires considerable adaptations of the pelvic and thigh muscles, leading to a different model for the blood supply of the anatomical structures involved. There are many anatomical variations of the femoral artery and its branches (HILL, 1972;TESTUT;LATARJET, 1979;BARBOSA, 2001;REARDON et al, 2004;FUKUDA et al, 2005;TANYELI et al, 2006;GETTY, 2008;KUMAR et al, 2011;OTAG et al, 2012;AVERSI-FERREIRA et al, 2013), but no reference is done to possible association with evolutionary aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The variations of the vessels of lower limb have been described as abnormal development of the arteries of the lower limb in the embryo [6]. It has been reported that, in the lower animals, the DFA originates from the internal iliac artery (IIA).…”
Section: Discussionmentioning
confidence: 99%